﻿Karyotype of Sabanejewiabulgarica (Drensky, 1928) (Teleostei, Cobitidae) from the Danube Delta, Romania - Hnátková, Eva; Majtánová, Zuzana; Bohlen Šlechtová, Vendula; Bohlen, Joerg; Ráb, Petr (Comparative cytogenetics, 2023)
The karyotype of the freshwater fish Sabanejewiabulgarica (Drensky, 1928), from the Danube Delta, was studied by conventional Giemsa staining and the C-banding technique. The diploid chromosome number was 2n = 50. The karyotype contained 2 pairs of metacentric (the first one was much larger than the second one), 6 pairs of submetacentric and 17 pairs of subtelocentric to acrocentric chromosomes. Pericentromeric blocks of heterochromatin were revealed in most of the chromosome pairs. The karyotype phenotype of S.bulgarica was the same as found for S.balcanica from Northern Carpathian Mountains.
Keywords: cobitoid loaches; Chromosome number; C-heterochromatin; karyotype structure